PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP MINAT BELI PELANGGAN PT.GAJAH TUNGGAL, TBK - Nurhikmah; Arry Dwi Syahputra (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
To determine the influence of service quality and price on interest in purchasing customer PT. Gajah Tunggal, Tbk. The research method uses qualitative and quantitative descriptive analysis. The population in this study were customer PT. Gajah Tunggal, Tbk. in Bekasi City. Based on the guidelines for determining the number of samples according to Roscoe. The analytical method used is simultaneous and partially linear regression. Result the of service quality and price have a positive and significant effect on interest in purchasing customer PT. Gajah Tunggal, Tbk, both simultaneous and partially.